Blood loss in coronary artery bypass grafting on minimally invasive extracorporeal circulation - a single-centre experience and retrospective analysis - Juchelka, Jan; Simek, Martin; Sabacky, Dominik; Vicha, Marek; Barshatskyi, Artur; Zuscich, Ondrej; Troubil, Martin; Hajek, Roman; Zapletalova, Jana; Santavy, Petr (Biomedical papers, 2025)
Background. Minimally-invasive extracorporeal circulation (MiECC) is confirmed to mitigate the post-perfusion syndrome resulting in better outcomes in operated patients compared to the conventional cardiopulmonary bypass (ECC).Aims. To determine whether there is a clinical benefit of lower blood loss in patients operated on MiECC compared to ECC. To provide a detailed construction of modified MiECC and its perfusion management.Methods. Retrospective analysis of the clinical data of 60 patients undergoing coronary artery bypass grafting on MiECC or ECC. The primary outcome was to compare the following variables in the 2 groups: intraoperative and 30-day mortality and cardiovascular death, myocardial infarction and cerebral stroke (MACCE). Secondary outcomes included surgical revision for bleeding or tamponade, intraoperative and postoperative blood loss and the consumption of packed red blood cell units. We modified our MiECC by connecting a cardiotomy suction.Results. There was no mortality, major adverse events or surgical revisions in either group. No difference was found for intraoperative blood loss. The MiECC group had significantly lower overall postoperative blood loss (660 mL vs 765 mL, P=0.037). Total consumption of packed red blood cell units was insignificantly higher in the ECC group (n=30 vs n=20, P=0.490).Conclusion. MiECC is a safe alternative to conventional ECC in routine procedures such as CABG. Its improved biocompatibility was reflected by better preservation of hemostasis in this study.
Keywords: coronary artery bypass grafting; extracorporeal circulation; minimal invasive; blood loss